Dinamika Perubahan Lahan dan Keanekaragaman Burung Dalam Ragam Tutupan Lahan di Cangkringan, Sleman, Yogyakarta.: Land Change Dynamics and Bird Diversity in a Variety of Land Cover in Cangkringan, Sleman, Yogyakarta - Dewi, Nabila Aulia; Herdiansyah, Dedy Setyo; Dira, Dira; Nugraha, Nanda Satya (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Indonesia is a country with abundant natural resources, one of which is green open spaces and vegetation. Land use change dynamics are the result of economic needs arising from development and community activities. This study was conducted to determine land use change dynamics and bird diversity as bioindicators of these changes. Land use change dynamics were mapped using remote sensing and satellite image analysis. The methods used in this research include field data collection on land cover and bird diversity, as well as analysis of diversity indices (H'), richness (R), and evenness (E) to evaluate biodiversity conditions. The study results show that vegetated areas experienced fluctuating increases (2014: 1,072.1 ha, 2019: 1,389.2 ha, and 2024: 1,538.8 ha), agricultural areas decreased (2014: 2,159.6 ha, 2019: 1,721.4 ha, and 2024: 1,538.8 ha), and built-up areas increased (2014: 1,295.1 ha, 2019: 1,721.4 ha, and 2024: 1,384.9 ha). The dynamics of change will affect bird diversity with values in vegetated areas H': 2.0532, agricultural areas H': 1.7350, and built-up areas H': 1.4415. Monitoring land changes is important as it is a key factor in regional spatial planning and one of the ways to protect existing green open spaces.